Migrants from Ukraine and Belarus Living in Sweden before the War - Fredrik W. Andersson; Eskil Wadensjö (Institute of Labor Economics (IZA), 2022)
The Russian war in Ukraine has led to many fleeing the country. The Temporary Protection Directive applies to those from Ukraine but also those who received a residence permit in Ukraine as a refugee before 24 February 2022, as those who have fled from Belarus to Ukraine in recent years. We can therefore expect that many refugees will come to Sweden from Ukraine, but also to a lesser extent indirectly from Belarus. For refugees originating in these two countries, reception may be facilitated by that people from the same countries have arrived before. Whether those who came earlier can be of help to refugees who come now in terms of finding employment depends, among other things, on the labor market position of the former migrants in Sweden. Do they have work and if so what kind of work? In which parts of Sweden do they live? In this paper, we try to answer these questions.
Keywords: F22; F51; J15; J21; J61; 330; Ukraine; Belarus; Swedish labor market; employment; migrants